Implementasi Pemahaman Zakat Pertanian Pada Petani Padi di Desa Hutaraja Kecamatan Panyabungan Selatan - Rizka Nasution; Yenni Samri Juliati Nasution (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This research aims to examine the implementation of understanding agricultural zakat among rice farmers in Hutaraja Village, South Panyabungan District. Agricultural zakat has an important role in ensuring social justice and economic prosperity for farmers, as well as supporting sustainable agricultural development. This research method includes in-depth interviews with rice farmers and zakat managers, as well as analysis of documentation related to the zakat program. The research results reveal that the implementation of understanding agricultural zakat in Hutaraja Village is not fully optimal. There are several obstacles, such as farmers' lack of understanding of the concept of agricultural zakat, lack of transparency in the collection and distribution of zakat, and the extent of the benefits of zakat for farmers that have not been achieved. This research proposes increasing understanding of agricultural zakat, training and education, increasing transparency in zakat management, as well as efforts to expand the positive impact of zakat for rice farmers. The implication of this research is the importance of increasing understanding and implementation of agricultural zakat as a tool to support farmer welfare and agricultural sustainability in the region.